Sustainability through website development: the case of public libraries in Malaysia - Abu Bakar, Ahmad Bakeri; J., Putri N. L. (ISAST, 2013)
With the introduction of the World Wide Web and gra phical browsers in the 1990s the Internet has become widely accessible and many people have grabbed the idea of using it for their multifarious purposes and age nda The library website is the most important window and the gateway for interactivity with the publics. So much so that higher quality websites tend to exhibit high traffi c pattern and are capable of attracting more links and thereby rendered those websites as h ighly visible. The question of visibility and accessibility is the refore important for any type of websites and should be addressed painstakingly with the noti on that sustainable development of the website may assist the library in reaching its goals. Through the development of quality websites libraries in Western countries are able to sustain their growth through generating income through charges, particularly for access to unique materials, making it attractive to sponsors or making it possible for t hird parties to deliver their own services based on website contents. It is the purpose of thi s paper to study on the question of visibility and accessibility of the websites of sel ected public libraries in Malaysia through the use of two major software, Alexa and EvaAcess .